Ecologia trófica de peixes anuais do Parque Nacional da Lagoa do Peixe - RS, por meio da metodologia isotópica - Defalco, Thaiane [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The fish of the family Rivulidae are characterized mainly by the small corporal size, for the marked sexual dimorphism and by the fact that they complete all his life cycle in temporary aquatic environment. Those environment shelter a great biodiversity of species, and many of those species, as well as the annual fish, present phases of their life cycles strongly associated to the drought regimes and flood. It is of fundamental importance for the conservation of those organisms and of their habitats, to understand the relations that establish among the different species and how they can interfere in the communities and in the ecosystems. This way, the current study's goal was to determine and compare the trophic niche of Austrolebias minuano and Cynopoecilus fulgens, two Rivulidae fish with occurrence in the South of Brazil. For such study we sampled fish and resources of four temporary ponds surroundings of Lagoa do Peixe National Park, Rio Grande do Sul. Through the analysis of isotope stable of carbon (δ13C) and nitrogen (δ15N) determined the niche isotope and the relationships trophic that settle down among those two species. The species presented high width of niche trophic and pronounced overlap. However, they were found solid differences of niche trophic among the ponds sampling. This way, the results of the current study indicate that the space heterogeneity among temporary aquatic habitats represents an important factor for the conservation of the Rivulidae species, because they guarantee the ecological variability among populations in the scale of the landscape, one of the basic conditions for species to survive in nature

Os peixes da família Rivulidae se caracterizam principalmente pelo pequeno tamanho corpóreo, pelo marcado dimorfismo sexual e por completarem todo seu ciclo de vida em ambientes aquáticos temporários. Esses ambientes abrigam uma grande biodiversidade de espécies, sendo que muitas dessas espécies, assim como os peixes anuais, apresentam fases dos seus ciclos de vida fortemente associada aos regimes de seca e cheia. É de fundamental importância para a conservação desses organismos e de seus ambientes, compreender as relações que se estabelecem entre as diferentes espécies e como elas podem interferir nas comunidades e nos ecossistemas. Deste modo o presente estudo teve como objetivo determinar e comparar o nicho trófico de Austrolebias minuano e Cynopoecilus fulgens, dois peixes Rivulidae com ocorrência no Sul do Brasil. Para tal foram amostrados peixes e recursos de quatro poças temporárias no entorno do Parque Nacional da Lagoa do Peixe, Rio Grande do Sul. Através da análise de isótopos estáveis de carbono (δ13C) e nitrogênio (δ15N) determinamos o nicho isotópico e as relações tróficas que se estabelecem entre essas duas espécies. As espécies apresentaram elevada amplitude de nicho trófico e pronunciada sobreposição, entretanto, foram encontradas diferenças consistentes de nicho trófico entre os banhados amostrados. Os resultados do presente estudo indicam que a heterogeneidade espacial entre ambientes aquáticos temporários representa um importante fator para a conservação das espécies de Rivulidae, pois garantem a variabilidade ecológica entre populações na escala da paisagem e consequentemente a manutenção das espécies na natureza
Keywords: Ecologia; Peixe; Peixe - Ecologia; Nicho (Ecologia); Isótopos estáveis; Rio Grande do Sul; Brasil